Spatiotemporal Mapping Techniques Show Clozapine Impairs Neurogenic and Myogenic Patterns of Activity in the Colon of the Rabbit in a Dose-Dependent Manner - Every-Palmer, Susanna; Lentle, Roger G.; Reynolds, Gordon; Hulls, Corrin; Chambers, Paul; Dunn, Helen; Ellis, Pete M. (Frontiers in Pharmacology, 2017)
Abstract Background: Clozapine, an antipsychotic used in treatment-resistant schizophrenia, has adverse gastrointestinal effects with significant associated morbidity and mortality. However it effects on defined patterns of colonic contractile activity have not been assessed. Method: We used novel radial and longitudinal spatiotemporal mapping techniques, combined with and monitoring of ambient lumen pressure, in ex vivo preparations of triply and of singly haustrated portions of rabbit colon colon to identify the contractile patterns of mass peristalses, fast phasic, and ripple contractions and to directly qualify the effects of clozapine at concentrations of 10µmol/L, 20µmol/L and 30µmol/L and of norclozapine. The effects of carbachol, serotonin and naloxone on clozapine-exposed preparations were also determined. Tetradotoxin was used to distinguish neurogenic from myogenic contractions. Results: At 10µmol/L, Clozapine temporarily abolished the longitudinal contractile components of mass peristalsis, which on return were significantly reduced in number and amplitude, as was maximal mass peristaltic pressure. These effects were reversed by carbachol (1µmol/L) and to some extent by serotonin (15µmol/L). At 10µmol/L, myogenic ripple contractions were not affected. At 20µmol/L clozapine had a similar but more marked effect on mass peristalses with both longitudinal and radial components and corresponding maximal pressure greatly reduced. At 30µmol/L, clozapine suppressed the radial and longitudinal components of mass peristalses for over 30 minutes, as well as ripple contractions. Similar dose related effects were observed on addition of clozapine to the mid colon. At 20µmol/L norclozapine had opposite effects to those of clozapine, causing moderate, but sustained, increases in the amplitudes of neurogenic and myogenic contractions. These slightly augmented contractions were abolished on addition of clozapine. Concentrations of norclozapine below 20µmol/L had no discernible effects. Conclusion: Clozapine, but not norclozapine, has potent effects on the motility of the rabbit colon, inhibiting neurogenic contractions at lower concentrations and myogenic contractions at higher concentrations. This is the likely mechanism for the serious and life-threatening gastrointestinal complications in human clozapine-users. These effects appear to be mediated by cholinergic and serotonergic mechanisms. Spatiotemporal mapping is useful in directly assessing the effects of pharmaceuticals on particular patterns of gastrointestinal motility.